Emissão de óxido nitroso associado ao uso de ureia no cultivo de melão amarelo - Segundo, Vanessa Cláudia Vasconcelos (2015)
The melon is a vegetable of great importance for the Brazilian Northeast: the region largest national producer. However, to obtain high productivity requires the use of inputs that can be harmful to the environment; of these, nitrogen fertilizers. These fertilizers release nitrous oxide, a greenhouse gas responsible for global warming. Given the importance of climate change, this paper proposes to assess the emission of nitrous in oxide yellow melon 'Goldex' cultivation fertilized with nitrogen fertilizer, at 5 and 15 days after transplanting. The experiment was conducted in a completely randomized design (CRD) with five replications. The four treatments were defined as follows: 0 (control), 1.0; 1.5 to 2 times the amount of nitrogen is recommended for each stage of this culture mentioned above. The variables analyzed were leaf area, leaf number, shoot dry weight, dry weight of the fruit, dry mass of roots, nitrous oxide flow, total soil nitrogen, plants and N (NH4+ and NO3-) soil. The variables related to plant development were subjected to regression analysis and descriptive analyzes were used (mean ± standard error) for checking the nitrous oxide flow behavior. The treatments significantly affected leaf area, leaf number, dry weight of shoots, dry mass of roots, nitrogen from the shoot, nitrogen from the root of the plants and soil nitrogen. For these variables the quadratic regression model was the best fit to explain the variation of the same from the absence and presence of nitrogen fertilization. Nitrous oxide flow had irregular temporal behavior during the phase of seedlings and growing during the flowering phase. The balance of applied N revealed that only a small portion of the nutrient was recovered. The application of nitrogen in higher than recommended dosages, did not increase the production of melon. Similarly, the calculation of the emission factor showed that the emissions of nitrous oxide (N2O) in the treatments did not reach values harmful to the environment.